Exploring Quantum Tunability in Novel Hybrid Dielectric-Ferroelectric-Multiferroic Materials for Advanced Photonic Applications - Zhang Tanuza; Das Tiffany; Chao Vickie (Yayasan Adra Karima Hubbi, 2024)
Dielectrics, ferroelectrics, and multiferroics are critical materials in modern technology due to their unique electrical, magnetic, and optical properties. Hybrid materials that combine these properties hold promise for advanced photonic applications. Quantum tunability, the ability to control material properties at the quantum level, offers opportunities to enhance performance and functionality in these hybrid materials. This study aims to investigate the potential of quantum tunability in novel hybrid dielectric-ferroelectric-multiferroic materials for advanced photonic applications. The research seeks to understand how combining these materials at the quantum level can lead to new functionalities and improved performance in photonic devices. A comprehensive approach was used, combining experimental and theoretical techniques. Hybrid materials were synthesized using epitaxial growth and chemical vapor deposition. X-ray diffraction, scanning electron microscopy, and spectroscopy characterized their structural, electrical, and optical properties. Quantum mechanical simulations were conducted to understand the interactions at the atomic level and predict material behavior under various conditions. The study demonstrated that hybrid materials exhibit unique properties that are not present in individual components. Enhanced dielectric and ferroelectric responses and improved magnetic and optical characteristics were observed. Quantum simulations revealed strong coupling between different ferroic orders, leading to tunable properties suitable for photonic applications. These findings were confirmed by experimental data, showing significant potential for these materials in advanced photonic devices. Quantum tunability in hybrid dielectric-ferroelectric-multiferroic materials offers a new pathway for developing advanced photonic applications. Integrating multiple ferroic properties at the quantum level enhances performance and new functionalities. Further research is needed to optimize these materials and address challenges related to stability and integration with existing technologies. This study provides a foundation for future photonics and multifunctional material design advancements.